Wizja roli i pozycji społecznej prawników w USA według Alexisa de Tocqueville’a a amerykański dyskurs prawniczy - Srokosz, Jacek (Wydawnictwo Uniwersytetu Wrocławskiego, 2020)
The subject of the study is the vision of the role and position of social lawyers in the United States according to Alexis de Tocqueville and its place in contemporary American legal discourse. Despite the passage of almost 200 years since the first edition of the work of the French philosopher On Democracy in America, many of his diagnoses regarding the percep-tion of the position of lawyers in America remain valid and many researchers have voiced that he predicted the gradual expansion of the political power of American courts. De Tocqueville described lawyers as a new aristocratic elite in a democratic society because, as he argued, only they could act as supervisors, teachers and educators for the lower classes. Lawyers’ predispositions to perform these social roles were to result from their professional know-ledge inaccessible to laymen from outside the legal environment, as well as from possessing certain features of the mind, passion for order, hostility toward revolution and contempt for the people’s emotions, which was connecting lawyers with the European aristocratic layer. Moreover, according to de Tocqueville, the American system itself, putting law and the Constitution in the center, gave lawyers a special role in social life. De Tocqueville’s arguments were eagerly accepted and developed in the American legal discourse, where in many cases they are present in an unmodified form to this day. The purpose of the study is to indicate the reasons why they enjoy such popularity and adequacy in contemporary American legal discourse. The author points out that, on the one hand, de Tocqueville in his analyzes indeed reflected the essence of the American systemic experiment, and on the other, his theses serve lawyers to build their own identity and internal integration, but also to legitimize their social position. The term “lawyer” is used here in the Polish meaning — including representatives of all legal professions.
Keywords: Tocqueville, Alexis de (1805-1859); amerykański dyskurs prawniczy; arystokracja; demokracja; prawnik